Wh-movement and the theory of feature-checking - Simpson, Andrew, 1962- (J. Benjamins Pub. Co., 2000)
Wh-movement and the theory of feature-checking argues that cross-linguistic variation in wh-constructions reduces to the availability of different lexical instantiations of a +wh C0 both across languages and within a single language, and the way in which such lexical elements are syntactically identified, either via movement or base-generation. Evidence from a wide range of patterns including wh-expletive questions leads to the conclusion that wh-feature checking may sometimes be effected non-locally and 'at a distance' (long-distance wh-agreement), and that movement in general takes place for.